The Impact of Modern Coconut Oil Packaging Training on Consumers’ Behaviors - Gideon Maige Gibai; Shima Dawson Banele (Indonesian Journal of Social Research (IJSR), 2023)
The local coconut oil producers at Kisutu Market, Dar es Salaam faced difficulties in deploying the modern packaging components due to knowledge and skills gaps henceforth low market value was experienced greenlighted the training for awareness creation. Assessment on impact of the training on the changes of the producers’ practices and its significances to the consumers were made by engaging 112 respondents categorically distributed into 102 coconut oil consumers and 10 producers. Data were collected using four ranked Likert scale questionnaire and semi-structure interview followed by the descriptive analysis. The findings proved that the training assisted the local coconut producers to utilize modern packaging henceforth impacted the consumers behaviours; enhanced communication; improved market experiences; fostered branding initiatives; assurance to the product quality and quantity; competition differentiation; attracting the shelves and easier pointing the coconut oil during purchasing under pressure; increased competitiveness of the coconut oil choices in supply chain. Moreover, the contributions are made to the literature of coconut oil, local producers and consumers and practitioners to continue to invest in awareness creation through trainings, accommodation of new knowledge and skills pertained the deployment of innovative packaging that positively turn the image of coconut oil product for valuable market and sustainability.